2013
DOI: 10.1200/jco.2013.51.7250
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Failure Rate After Preoperative Chemoradiation of Esophageal Adenocarcinoma and the Outcomes of Salvage Strategies

Abstract: A B S T R A C T PurposeThe primary purpose of surveillance of patients with esophageal adenocarcinoma (EAC) and/or esophagogastric junction adenocarcinoma after local therapy (eg, chemoradiotherapy followed by surgery or trimodality therapy [TMT]) is to implement a potentially beneficial salvage therapy to overcome possible morbidity/mortality caused by locoregional failure (LRF). However, the benefits of surveillance are not well understood. We report on LRFs and salvage strategies in a large cohort. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 22 publications
(9 reference statements)
2
63
0
9
Order By: Relevance
“…16 We previously reported that the rate of LR is low (approximately 5%) after TMT for esophageal and gastroesophageal junction adenocarcinoma. 1 However, the rate of persistent cancer or locally recurrent cancer after BMT can be as high as 50%. 5,18,19 To our knowledge, the value of aggressive surveillance in terms of the success of implementation of salvage strategies has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 We previously reported that the rate of LR is low (approximately 5%) after TMT for esophageal and gastroesophageal junction adenocarcinoma. 1 However, the rate of persistent cancer or locally recurrent cancer after BMT can be as high as 50%. 5,18,19 To our knowledge, the value of aggressive surveillance in terms of the success of implementation of salvage strategies has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 The purpose of surveillance is to provide salvage therapy to patients who develop LR only. SS for LR only after BMT is recommended if surgery is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Most studies published previously have also shown a reduction in LRR after preoperative CRT for esophageal cancer compared to surgery alone. 26,29,37,38 The LRR rates range from 5% to 14% and 34% to 42% after neoadjuvant CRT and surgery alone, respectively. 26,29,37,38 The recurrence outcomes in the CROSS study showed that preoperative CRT reduced the overall recurrence rate (surgery 58% vs preoperative CRT 35%) and that preoperative CRT reduced LRR from 34% to 14% (P,0.001) and peritoneal carcinomatosis from 14% to 4% (P,0.001).…”
Section: Multimodal Therapy For Esophageal Cancermentioning
confidence: 99%